2022
DOI: 10.3389/fmed.2022.883028
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death in Sepsis Associated Acute Kidney Injury

Abstract: Sepsis-associated acute kidney injury (SA-AKI) is common in patients with severe sepsis, and has a high incidence rate and high mortality rate in ICU patients. Most patients progress to AKI before drug treatment is initiated. Early studies suggest that the main mechanism of SA-AKI is that sepsis leads to vasodilation, hypotension and shock, resulting in insufficient renal blood perfusion, finally leading to renal tubular cell ischemia and necrosis. Research results in recent years have shown that programmed ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 167 publications
(185 reference statements)
0
17
0
Order By: Relevance
“…Autophagy-mediated lysosomal degradation and the ubiquitin proteasome system are two major pathways that maintain intracellular homeostasis by removing damaged organelles and misfolded proteins ( Xu et al, 2020 ). Selective autophagy also regulates ferroptosis by degrading GPX4 ( Wu et al, 2022 ). Therefore, the co-targeting of autophagy and GPX4 could function synergistically to kill BC cells ( Sun et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy-mediated lysosomal degradation and the ubiquitin proteasome system are two major pathways that maintain intracellular homeostasis by removing damaged organelles and misfolded proteins ( Xu et al, 2020 ). Selective autophagy also regulates ferroptosis by degrading GPX4 ( Wu et al, 2022 ). Therefore, the co-targeting of autophagy and GPX4 could function synergistically to kill BC cells ( Sun et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that inflammatory factors can directly promote apoptosis, further aggravating sepsis-induced lung injury 26 . In addition, pyroptosis has been thought to be involved in septic ALI [27][28][29] . Therefore, this study focused on exploring the effects of circPTK2 on pyroptosis and inflammation in septic ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis-related apoptosis is morphologically distinct from apoptosis, which is closely associated with inflammation [ 65 ] and is characterized by rupture of the plasma membrane, leakage of cell contents, and swelling of organelles. [ 66 ] Necroptosis is not dependent on cystathionine but is regulated through the involvement of multiple cellular signaling proteins, including receptor-interacting protein kinase 1, receptor-interacting protein kinase 3 (RIPK3) and its downstream target, and the mixed-spectrum kinase structural domain (MLKL). [ 67 ] Many cellular mediators can activate necrotrophic apoptotic pathways such as death receptors, interferons, toll-like receptors and RNA or DNA sensors.…”
Section: Microrna Crosstalk With Pcd In Renal Diseases and Clinical A...mentioning
confidence: 99%